PENGEMBANGAN KAWASAN PEDESAAN BERBASIS KOMODITI UNGGULAN DI KECAMATAN PINOGU - Paramata, Sri Hantuti; Lopo, Asmiati (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2023)
This study aims to map the Pinogu District area as an isolated and difficult to reach area. Identifying the economic potential of Pinogu Subdistrict to increase significant economic growth. Pinogu Subdistrict, which has five villages with an area of 405.96, is an economic area that has the potential for commodities to develop, especially agricultural commodities, plantations and fruits. Based on the results of the analysis, it shows that the leading commodities for the development of rural areas are rice, plantation products, and coffee. The various leading commodities are spread across five villages in Pinogu District. The economic growth of Pinogu District is classified as very slow to grow, this is due to the high cost economy which causes the economic turnover to be very slow. Based on the results of the analysis, the cause of this is because transportation access to enter and exit goods and people in the Pinogu area is very difficult because the only transportation owned in this region is two-wheeled (motorbikes/motorcycle taxis).